Posttraumatic stress disorder following political imprisonment: the role of mental defeat, alienation, and perceived permanent change. - Ehlers, A; Maercker, A; Boos, A (2000)
An interview study of 81 former political prisoners investigated whether posttraumatic stress disorder (PTSD) is related to the way individuals process the prison experience. In contrast to participants without PTSD, those with chronic or remitted PTSD were more likely to perceive mental defeat and an overall feeling of alienation from other people. Chronic PTSD was also related to perceived negative and permanent change in their personalities or life aspirations. The groups did not differ in their attempts to gain control during imprisonment. Evidence for a relationship between political commitment and PTSD was mixed. The results suggest that mental defeat, alienation, and permanent change are related to PTSD after interpersonal trauma and may need to be addressed in treatment.